Analysis of the scientific production on feedback on teaching English as a foreign language using ERIC database (Acta Scientiarum. Education, 2017)
Feedback is one of the most significant tools on learning, teaching, developing autonomy, self-efficacy and achievement in the educational environment. Its importance is emphasized in articles, dissertations and theses; however, a very little number of them have been published recently. This article intends to verify in what perspective feedback has been examined, in what ways it has been revealed to be effective for students and teachers to reach their goals and identify possible gaps of study that need to be fulfilled in future researches. In order to carry out this investigation, this study examined articles, papers and theses published from 2006 to 2015 about feedback in courses of English as a foreign language (EFL), using ERIC database. Our findings were organized into six categories: corrective feedback in oral interaction; effects of peer feedback; feedback expectancy; teachers’ conceptions of intelligence and their relations in offering feedback; the effect of different types of feedback strategies on written texts; the use of feedback through technology. The results indicate that feedback is a crucial tool in the educational process and it plays a central role in learning a foreign language. Further investigations concerning feedback are suggested.